2020
DOI: 10.1021/acsami.0c01023
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Metal–Organic Framework d-His-ZIF-8@SiO2 Core–Shell Microspheres Used for HPLC Enantioseparations

Abstract: Chiral metal–organic frameworks (MOFs) have aroused great attention in the chiral separation field based on their excellent characteristics, including abundant topological structures, large surface area, adjustable pore/channel sizes, multiple active sites, and good chemical stability. However, the irregular morphology and nonuniformity of the synthesized MOF particles cause low column efficiency and high column backpressure for MOF-packed columns, which significantly affects their separation performance. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(36 citation statements)
references
References 39 publications
(58 reference statements)
0
36
0
Order By: Relevance
“…[21] Furthermore, when TAMOF-1 crystals served as the CSP, they proved to have excellent chiral discrimination toward racemic trans-2,3-diphenyloxirane and the ability to separate racemates of other chiral compounds including 1-phenylethanol, benzoin, and flavanone, which outperformed several commercial chiral HPLC columns. Homochiral D-His-ZIF-8@SiO 2 microspheres were utilized as CSP by Yu et al [91] Homochiral D-His-ZIF-8 was in situ grown on Zn-BLD Methyl phenyl sulfoxide Baseline separation [86] [ZnLBr]•H 2 O Ibuprofen, 1-phenyl-1-propanol, 1-phenylethylamine and benzoin…”
Section: High-performance Liquid Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…[21] Furthermore, when TAMOF-1 crystals served as the CSP, they proved to have excellent chiral discrimination toward racemic trans-2,3-diphenyloxirane and the ability to separate racemates of other chiral compounds including 1-phenylethanol, benzoin, and flavanone, which outperformed several commercial chiral HPLC columns. Homochiral D-His-ZIF-8@SiO 2 microspheres were utilized as CSP by Yu et al [91] Homochiral D-His-ZIF-8 was in situ grown on Zn-BLD Methyl phenyl sulfoxide Baseline separation [86] [ZnLBr]•H 2 O Ibuprofen, 1-phenyl-1-propanol, 1-phenylethylamine and benzoin…”
Section: High-performance Liquid Chromatographymentioning
confidence: 99%
“…Highest α ranging from 11.6 to 13.2 for chiral sulfoxides [90] D-his-ZIF-8@SiO 2 1-(1-Naphthyl)ethanol, benzoin, praziquantel, 1,1´-bi-(2-naphthol), trans-stilbene oxide, naproxen, 1-(9-anthryl)-2,2,2-trifluoroethanol and zopicloneBaseline separation for most analytes. Highest α of 7.13 for 1-(1-naphthyl)ethanol[91]…”
mentioning
confidence: 98%
“…Core-shell microspheres have also been developed for use as CSPs in HPLC enantioseparations, which build upon the previous ideas of MOF-silica composites. [22] These particles, synthesised by incorporating silica microspheres into the reaction mixture of histidine-modified ZIF-8, exhibited a uniform diameter of 5.5 μm, perfect for utilization as CSPs without any manual grinding. The resulting HPLC columns separated a total of eighteen racemates with separation factors up to 7.55, the highest yet documented.…”
Section: Frameworkmentioning
confidence: 99%
“…So far, a few examples of chiral MOF@SiO 2 core-shell composites as CSPs for HPLC enantioseparation. Recently, our group reported that two kinds of chiral MOF@SiO 2 core-shell composites including d-his-ZIF-8@SiO 2 [34] and [Co 2 (d-cam) 2 (TMDPy)]@SiO 2 [20] via an in-situ growth method used as CSPs for HPLC separation of racemates. These chiral MOF@SiO 2 core-shell composites packed columns exhibited high enantioselectivity and excellent chiral resolution ability toward many different kinds of enantiomers such as alcohols, amines, phenols, ketones, organic acids, organic bases, and so on.…”
Section: Introductionmentioning
confidence: 99%